Design and development of IoT based comprehensive system for emergency assistance - Habib, Sahriar; Afnan, Zawata; Chowdhury, Sakib Anam; Chowdhury, Sarah Altaf (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.